2009
DOI: 10.1016/j.jcmg.2008.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Myocardial Perfusion Correlate With Deterioration of Left Ventricular Systolic Function in Chronic Chagas' Cardiomyopathy

Abstract: In CCC patients, the progression of left ventricular systolic dysfunction was associated with both the presence of reversible perfusion defects and the increase in perfusion defects at rest. These results support the notion that myocardial perfusion disturbances participate in the pathogenesis of myocardial injury in CCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0
54

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 22 publications
6
39
0
54
Order By: Relevance
“…The individual increase in the perfusion defect area at rest (possibly indicating the presence of fi brosis) was signifi cantly correlated with the corresponding reduction in LV ejection fraction (with a mean decrease over time in the entire group of patients from 55% ± 11% to 50% ± 13%). Hence, in this longitudinal study, the deterioration of LV systolic function over time was associated with both the presence of reversible ischemic defects at the initial assessment and an increase in the extent of irreversible perfusion defects during follow-up 50 .…”
Section: Coronary Microvascular Dysfunctionmentioning
confidence: 74%
See 1 more Smart Citation
“…The individual increase in the perfusion defect area at rest (possibly indicating the presence of fi brosis) was signifi cantly correlated with the corresponding reduction in LV ejection fraction (with a mean decrease over time in the entire group of patients from 55% ± 11% to 50% ± 13%). Hence, in this longitudinal study, the deterioration of LV systolic function over time was associated with both the presence of reversible ischemic defects at the initial assessment and an increase in the extent of irreversible perfusion defects during follow-up 50 .…”
Section: Coronary Microvascular Dysfunctionmentioning
confidence: 74%
“…This suggestion may indeed be the case based on a more recent study of 36 patients with serologically proven Chagas disease who were initially evaluated with Tc-99m-Sestamibi MPS at rest and during physical exercise and who had the nuclear examination repeated after a mean period of 5.6 years 50 . Of the 36 patients, 20 (56%) exhibited reversible ischemic myocardial perfusion defects involving an average of 10.2% ± 9.7% of the LV area, as determined by the SPECT technique.…”
Section: Coronary Microvascular Dysfunctionmentioning
confidence: 93%
“…The impairment of cardiac sympathetic function at the ventricular level that occurs early in the course of Chagas cardiomyopathy is related to regional myocardial perfusion disturbances (Hiss et al, 2009). This occurs before wall motion abnormalities can be demonstrated (Hiss et al, 2009;Simoes et al, 2000). In the same way, abnormal vasodilatation and vasoconstriction at the microcirculatory level may cause myocardial damage in patients with Chagas disease.…”
Section: Microvascular Abnormalities and Ischemiamentioning
confidence: 99%
“…In the same way, abnormal vasodilatation and vasoconstriction at the microcirculatory level may cause myocardial damage in patients with Chagas disease. Both conditions are associated with the progression of ventricular dysfunction (Hiss et al, 2009;Simoes et al, 2000). Transient microvascular ischemic disturbances of low intensity and short duration have been postulated to be the causative mechanisms of Chagas cardiomyopathy.…”
Section: Microvascular Abnormalities and Ischemiamentioning
confidence: 99%
“…Many investigators have found abnormal myocardial perfusion using isonitrile-99m-technetium (Castro R., et al, 1988) and thallium-201 (Hagar & Rahimtoola, 1991, MarinNeto, et al, 1992 scintigraphy in chagasic patients with normal epicardial coronary arteries. Furthermore, the progression of left ventricular systolic dysfunction is associated with both, the presence of reversible perfusion defects and the increase in perfusion defects at rest (Hiss, et al, 2009, Schwartz & Wexler, 2009. Anatomopathological studies in humans also provided evidence of microvascular damage in CCC.…”
Section: Microvascular Damagementioning
confidence: 99%